Rancang Bangun Sistem Pakar Diagnosis Penyakit Pada Sekitar Rahim Wanita - Bariyah, Choirul; Irawan, Jusak; Tjandrarini, A.B (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
The diseases around the woman's uterus is a fatal disease and causing death. But a lot of people underestimate the symptoms. The type of disease around the woman’s uterus have similar symptoms, it is difficult to know the type of disease that patients suffered. Therefore, patients need a doctor to consult about the disease around the woman's uterus. However, Patients often have trouble to consult a doctor because of limited working hours and cost limitations. In order to provide convenience consultation process, in this work, we build an expert system for diagnosing diseases around woman’s uterus using the certainty factor metho. The expert systems will diagnose any symptoms by providing certainty factor values at each symptom and the certainty factor value of answers. The new system will produce diagnosed diseases based on the some facts given by a user. The trial results showed that the system give accuracy diagnosis of 90%. It is examined by employing ten patients. This system also provide treatment advice based on the type of disease that suffered. However, the expert system for diagnosis of disease the woman's uterus can be accessed anytime and anywhere via website.